PENGARUH RASIO KEUANGAN TERHADAP KEBIJAKAN DIVIDEN DENGAN PERTUMBUHAN PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Unnisa', Mutiara Annafi'; Susilo, Dwi Ermayanti (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
This study analyzes the influence of profitability, leverage, and liquidity on dividend policy, with firm growth as an intervening variable, in coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 20202023 period. The research variables are proxied by Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR), Growth, and Dividend Payout Ratio (DPR). The study employs a quantitative method, analyzing data from 12 coal mining sub-sector companies listed on the IDX during the 20202023 period, selected using purposive sampling. The data analysis techniques include multiple linear regression and path analysis to examine mediation effects. The results show that return on equity and current ratio significantly affect dividend policy and firm growth. However, the debt-to-equity ratio does not considerably affect dividend policy, as high leverage increases interest burdens, limiting investment and dividend payments. Firm growth cannot mediate these relationships. Return on equity enhances dividend-paying capacity, a high debt-to-equity ratio restricts dividend payments, and the current ratio tends to be allocated to support firm growth.